Association between Expression of 8-OHdG and Cigarette Smoking in Non-small Cell Lung Cancer - Ae Ri An; Kyoung Min Kim; Ho Sung Park; Kyu Yun Jang; Woo Sung Moon; Myoung Jae Kang; Yong Chul Lee; Jong Hun Kim; Han Jung Chae; Myoung Ja Chung (Korean Society of Pathologists & the Korean Society for Cytopathology, 2019)
Background Exposure to cigarette smoking (CS) is a major risk factor for the development of lung cancer. CS is known to cause oxidative DNA damage and mutation of tumor-related genes, and these factors are involved in carcinogenesis. 8-Hydroxydeoxyguanosine (8-OHdG) is considered to be a reliable biomarker for oxidative DNA damage. Increased levels of 8-OHdG are associated with a number of pathological conditions, including cancer. There are no reports on the expression of 8-OHdG by immunohistochemistry in non-small cell lung cancer (NSCLC). Methods We investigated the expression of 8-OHdG and p53 in 203 NSCLC tissues using immunohistochemistry and correlated it with clinicopathological features including smoking. Results The expression of 8-OHdG was observed in 83.3% of NSCLC. It was significantly correlated with a low T category, negative lymph node status, never-smoker, and longer overall survival (p < .05) by univariate analysis. But multivariate analysis revealed that 8-OHdG was not an independent prognostic factor for overall survival in NSCLC patients. The aberrant expression of p53 significantly correlated with smoking, male, squamous cell carcinoma, and Ki-67 positivity (p < .05). Conclusions The expression of 8-OHdG was associated with good prognostic factors. It was positively correlated with never-smokers in NSCLC, suggesting that oxidative damage of DNA cannot be explained by smoking alone and may depend on complex control mechanisms.